The geodynamic evolution of the ferké shear zone (fsz): relative timing of the associated tectonic and magmatic events, North-Central Ivory Coast, West Africa - Mkentane, Andile Protas (My University, 2019)
The Palaeoproterozoic Baoulé-Mossi domain of the West African Craton in north-central Ivory Coast is crosscut by a north-northeast trending Ferké Batholith, confined by first-order crustal-scale Ferké Shear Zone (FSZ). To present a geodynamic evolution of the FSZ, incorporation of strato-tectonic, geophysical, geochemical, geochronological revisions is pivotal. In the study region, crosscutting relationship resolved that the oldest unit is formed by gneiss that is uncomfortably overlain by volcano-sedimentary sequences which are intruded by post-basin granitoids, i.e. Ferké Batholith. Volcano-sedimentary sequences consist of conglomeratesandstone-siltstone-mudstone succession and meta-volcaniclastic greywacke unit. Intrusive units making up Ferké Batholith include granodioritic gneiss, granodiorite, granite, tonalite, diorite and pegmatite. U-Pb zircon analysis of samples from the orthogneiss gave a crystallization age of the orthogneiss at 2282 ± 4 Ma, and these were affected by Dext extensional phase around 2132 ± 12 Ma that resulted in basin formation. Fining-upwards volcano-sedimentary sequences were deposited in the extensional-subsiding setting between 2109–2079 Ma. At 2097 Ma, Ferké Batholith emplacement was coeval with the formation of the FSZ. Four main deformational events were recognised crosscutting these rock units. D1 is a progressive deformation event that is dominated by ductile-brittle structures that formed at ~2097 Ma, and is responsible for development of north-northeast trending sinistral shear zones, steeply dipping foliation (S1 and S1-C), sub-horizontal L1 lineation and tight F1 folds. Ferké Batholith emplacement is constrained between 2097 and 1842 Ma U-Pb ages supported by crosscutting relationships. U-Pb age of 2097 Ma constrains D1 and minimum age for deposition of metasedimentary units. Late D1 structures are defined by northwest trending sub-vertical displaced fractures. Northwest trending dilational jogs and sigmoidal en-echelon fractures were formed during late D1. D1 event is related to north-northwest and south-southeast directed principal compressive strain axis. The D2 structures comprise northwest trending F2 folds and foliation (S2) from refolding of D1 structures S1 and F1. Dextral sense of displacement from north-northeast trending shear zones and L2 lineation along the Ferké-Bandama branch developed during D2. West, northwest and west-northwest trending veins (V2) are associated with D2 deformation. Kinematic analysis indicated that the principal compressive strain axis was northnortheast or northeast directed during D2 deformation. iii Brittle fractures, including the northwest to west trending fractures and faults formed the third generation of structure (D3). The traces of D3 structures crosscut those of D1 and D2 features throughout the study area. Northwest sinistral en echelon structures and northeast trending displaced fractures correlate with D3 characteristics i.e. overall north-northeast to northeast maximum shortening direction. Geochemical data show that various granitoids making up the Ferké Batholith are true granites. These intrusive units geochemical character shows calc-alkaline affinities with a very high-K character, mostly I-type and peraluminous composition. Tectonic discrimination diagrams confine the batholith within syn-collision fields. Gold mineralisation associated with FSZ occurs in the metasedimentary units to the southwest (Tortiya region) and northeast (north of Kouloukorosso) of the Ferké Batholith. These regions are structurally controlled and spatially associated with FSZ and hydrothermal veins that formed in response to the regional extensional stress field. The shape of the batholith and/or shear zone sense of displacement permits releasing bends (normal faults) to develop in the regions of Tortiya and Kouloukorosso.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Geology to the Faculty of Science, at the University of the Witwatersrand, 2019
Keywords: Geology; Geodynamics; Magmatism